Pengaruh Flash Sale dan Diskon terhadap Impulsive Buying pada Produk Fashion di Shopee - Utami, Cahyaning; Savitri, Citra; Pramudita Faddila, Syifa (Journal of Management and Bussines (JOMB), 2024)
This study aims to measure the extent to which flash sales and discount offers influence impulsive buying decisions. Data were collected through an online survey involving 130 respondents and analyzed using quantitative descriptive methods and Structural Equation Modeling - Partial Least Squares (SEM-PLS) to evaluate the significant effect of flash sales and discounts on impulsive buying. The results showed that marketing strategies involving flash sales and discounts significantly stimulated quick and spontaneous purchasing decisions. This finding highlights the effectiveness of these marketing techniques in increasing consumer impulsive behavior in the fashion category. Keywords: Discount, Flash Sale, Impulsive Buying